PENGARUH LABEL HALAL DAN CELEBRITY ENDORSMENT, CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Ayif fathurrahman; Ambar Arum Pratiwi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to examine the effect of the halal label and celebrity endorsment on purchasing decisions through brand image. This study uses a research method of proposive sampling used to collect quantitative data. This study uses primary data, by distributing questionnaires to students who use cosmetic wardah products with the amount of data processed by 100 respondents. There are 2 variables used in this study, namely the independent and dependent variables. The independent variables of this study consist of the halal label, celebrity endorsment, and brand image. The dependent variable of this study is the purchase decision. The data research method used a Likert scale questionnaire. The analytical tool used is the validity test, reliability test, classical assumption test, multiple linear regression test, T-test and F test and the coefficient of determination (R2). The result of this research is that Halal Label has an effect on Purchase Decision, Celebrity Endorsment has an effect on Purchase Decision, Brand Image has an effect on Purchase Decision.